Gendered Language - Pamela Jakiela; Owen Ozier (Institute of Labor Economics (IZA), 2020)
Languages use different systems for classifying nouns. Gender languages assign nouns to distinct sex-based categories, masculine and feminine. We construct a new data set, documenting the presence or absence of grammatical gender in more than 4,000 languages which together account for more than 99% of the world's population. We find a robust negative cross-country relationship between prevalence of gender languages and women's labor force participation and educational attainment. We replicate these associations in four countries in Sub-Saharan Africa and in India, showing that educational attainment and female labor force participation are lower among those whose native languages use grammatical gender.
Keywords: J16; Z10; Z13; 330; grammatical gender; language; gender; linguistic determinism; labor force participation; educational attainment; gender gaps